(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2017)
This study focused on a fundamental issue which was represented by ability of Iraqi central bank in facing the difficulty of determining the optimal ratio of liquidity in the Iraqi banks in terms of the balancing between its obligations to the depositors and borrowers, and liquidate their funds on one hand and the risks on the other hand.the search aimed for achieving the goals which represented by identifying the possibility of Iraqi banks to apply the regulations rules and instructions issued by central bank of Iraq in determining ratio of liquidity and its appropriate with Iraqi banks action to implement a reasonable profit to measure and analyze the legal liquidity ratio and employ these funds for the purpose of investing in profitable fields and then determine the size of the risks. to prove this research a sample was selected in a number of private Iraqi banks which are(Middle East Investment Bank, Commercial Bank of Iraq, North Bank for Finance and Investment, Al-Ahli Bank of Iraq, Gulf Commercial Bank,Bank of Babylon).By reviewing the annual reports of Iraqi banks research sample for the period (2005- 2013) the percentages has been extracted for each of legal liquidity ratio (liquid / liquid liabilities assets), liquidity ratio (cash / deposits), the ratio of profitability (net income / total assets), the ratio of the employment of funds (investments / total deposits) and the ratio of liquidity risk (total cash / total assets). Based on rated analytical results it has been reaching to an important number of conclusions which are: The contribution of the Iraqi Central Bank supervision in the development and growth of financial indicators, particularly the ratio of legal liquidity index and its suitability to the work of banks if the ratio was calculated according to the terms of a unified model contains vocabulary of numerator and denominator ratio by Iraqi banks (search sample).Then weset a number of recommendations which are :It is necessary for effective contribution of Iraqi central bank role to monitor the liquidity level in the Iraqi banks by developing a unified model to calculate the legal liquidity ratio in line with regulations rules and instructions issued by the Central Bank of Iraq and with the international standards and their suitability for banking.